Seasonal variation in physio-biochemical responses in osmanabadi goat kids: growth assessment by alkaline phosphatases as a biomarker - wankar, alok Khemraj; Kekan, Prakash Madhukarao; Daware, Sudhir Bapurao; Amrutkar, Suhas Ashokrao; Bhagat, Yogesh Deoram; Chobe, Poonam Hanumant; Pangaonkar, Laxmikant Ashokrao (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was planned to assess the impact of different seasons and temperature humidity index (THI) on physiology, metabolism, and growth performance in osmanabadi kids. For the study, 06 kids (0-3 months) were reared under a semi-intensive system and exposed to three different seasons, viz., summer (April-May), monsoon (July-August) and winter (December-January). Physiological and meteorological variables were recorded at weekly intervals, while for biochemical estimations, blood was collected, at a 15-day interval. Body temperature and respiration rates were higher in summer and winter, while the heart rate was highest during summer (P<0.05). Maximum body weight was seen in summer (P<0.05), followed by monsoon and winters, respectively. Serum protein, albumin, globulin, and phosphorus didn’t vary (P>0.05), but alkaline phosphatases (ALP) and calcium levels were significantly higher in summer and monsoon (P<0.05). It can be concluded that, despite high THI ranges (81-82), during summer and monsoon seasons which resulted in physio-biochemical alterations, the osmanabadi goat kids were able to maintain a steady growth rate, due to higher thermotolerance and are better adapted to regional climatic conditions. We also observed a notable positive correlation between ALP, calcium and growth and that serum ALP concentrations can be used as biomarker for measuring growth in osmanabadi goat kids.